CT-based delineation of organs at risk in the head and neck region: DAHANCA, EORTC, GORTEC, HKNPCSG, NCIC CTG, NCRI, NRG Oncology and TROG consensus guidelines. Issue 1 (October 2015) - Brouwer, Charlotte L.; Steenbakkers, Roel J.H.M.; Bourhis, Jean; Budach, Wilfried; Grau, Cai; Grégoire, Vincent; van Herk, Marcel; Lee, Anne; Maingon, Philippe; Nutting, Chris; O'Sullivan, Brian; Porceddu, Sandro V.; et al.
Abstract Purpose The objective of this project was to define consensus guidelines for delineating organs at risk (OARs) for head and neck radiotherapy for routine daily practice and for research purposes. Methods Consensus guidelines were formulated based on in-depth discussions of a panel of European, North American, Asian and Australian radiation oncologists. Results Twenty-five OARs in the head and neck region were defined with a concise description of their main anatomic boundaries. The Supplemental material provides an atlas of the consensus guidelines, projected on 1 mm axial slices. The atlas can also be obtained in DICOM-RT format on request. Conclusion Consensus guidelines for head and neck OAR delineation were defined, aiming to decrease interobserver variability among clinicians and radiotherapy centers.